Resolving cryptic diversity in the Chromis viridis species complex (Pomacentridae): a multilocus phylogenetic and morphometric reassessment of species boundaries - M. U. Rekha; Teena Jayakumar T. K.; Abhilash C. P.; Ahamed Rasheeq A.; Saikrishnan K. R.; Vallarasu R.; Gladston Y.; Kajal Chakraborty; Ajithkumar T. T. (Frontiers in Marine Science, 2026)
The blue-green damselfish, Chromis viridis (Cuvier, 1830), is widely distributed across Indo-Pacific coral reefs and is among the most heavily traded marine ornamental fishes. Recent molecular studies have suggested the presence of cryptic diversity within the C. viridis complex, but species boundaries remain unresolved. Multilocus phylogenetic analyses incorporating three mitochondrial markers—cytochrome c oxidase subunit I (COI), cytochrome b (cytb), and the mitochondrial control region (D-loop)—and two nuclear markers, recombination-activating gene 1 (RAG1) and recombination-activating gene 2 (RAG2), were performed to assess lineage diversification within the Chromis viridis species complex. Specimens collected from the Lakshadweep Archipelago and the Gulf of Mannar, India, formed a distinct and well-supported lineage that was clearly separated from C. viridis sensu stricto and other congeners in phylogenetic reconstructions and genetic distance analyses. Multiple species-delimitation approaches consistently supported the recognition of this lineage as an independently evolving taxon, and morphometric analyses revealed corresponding differences in body proportions and meristic characters. Based on the concordance of molecular and morphological evidence, a new species, Chromis veneta sp. nov., is herein described from the Indian Ocean. The new species differs from C. viridis in having a relatively elongate body, narrower caudal peduncle, distinctive body pigmentation, yellowish to orangish distal fin margins, and a deeply forked caudal fin with elongate lobe tips. Additional diagnostic features include differences in dentition, gill-raker counts and sagittal otolith morphology. The discovery of C. veneta sp. nov. highlights underestimated diversity within the C. viridis complex and underscores the importance of integrative taxonomy in revealing cryptic reef-fish diversity.

Unveiling Growth Patterns and Condition Status of 25 Flatfish Species (Order: Pleuronectiformes) from the Southern Coast of Tamil Nadu, India: Evidence from Length–Weight Relationships - R. G. Sasikumar; P. Jawahar; N. Jayakumar; G. Arul Oli; T. Ravikumar; M. Sharumathi; J. Joyson Paul; C. Abishek; Arnaa Armaan Muzaddadi (Thalassas: An International Journal of Marine Sciences, 2026)

Length–Weight Relationships and Condition Factor of Fourteen Clupeiform Fishes from the Gulf of Mannar, Southeast Coast of India - M. Armaan Arnaa; N. Jayakumar; R. Durairaja; M. Kalaiarasan; K. Karuppasamy; C. Abishek; M. Sharumathi; J. Joyson Paul; R. G. Sasikumar (Thalassas: An International Journal of Marine Sciences, 2026)

Deciphering Environmental Drivers on Plankton Dynamics in Punnakayal–Pazhayakayal Estuarine Complex, Southern Coast of India - Kamei Ringjonmeilu; N. Jayakumar; R. Durairaja; V. Rani; T. Ravikumar; R. Saravanan; C. Sudhan; Adyasha Sahu; J. Joyson Paul; S. Parkavi (Thalassas: An International Journal of Marine Sciences, 2026)

Comparative Assessment of Length-Weight Relationship and Relative Condition Factor of 25 Grouper Species along the Southern Coast of Tamil Nadu, India - J. Joyson Paul; R. Durairaja; N. Jayakumar; N. Daniel; T. Ravikumar; M. Sharumathi; R. G. Sasikumar; C. Abishek; Arnaa Armaan Muzaddadi (Thalassas: An International Journal of Marine Sciences, 2026)

Demographic Characteristics and Exploitation Status of the Blue Swimming Crab Portunus pelagicus (Linnaeus, 1758) Along the Palk Bay Coast, Southeast India - Pearlin Arul Granap S.; Durairaja R.; Jayakumar N.; Ranjith L.; Sudhan C.; Karuppasamy K.; Kalaiarasan M.; J. Joyson Paul; Nandhakumar M. (Thalassas: An International Journal of Marine Sciences, 2025)

Tailoring CdSe nanoparticles at different pH levels for improved methylene blue photodegradation - X. Venci; Amal George; Mohammed Alsawat; S. Rahul; Subhav Singh; Sivarasan Ganesan; C. Dominic Savio; A. Dhayal Raj; S. John Sundaram; G. Jayakumar (Environmental Geochemistry and Health, 2025)

Substrate Effect on the Contribution of Ammonium and Urea to Marine Nitrification and Nitrous Oxide Production - Weiyi Tang; Catherine Hexter; Rongbo Dai; Samantha G. Fortin; John C. Tracey; Naomi Intrator; Moriah A. Kunes; Xianhui S. Wan; Amal Jayakumar; Dalin Shi; Bess B. Ward (Environmental Microbiology, 2025)
Nitrification (microbial oxidation of ammonia to nitrite and nitrate) controls nitrogen speciation and is the main source of nitrous oxide (N 2 O) in the ocean. It was recently shown that the most abundant marine ammonia oxidizers, the ammonia‐oxidising archaea (AOA), are also capable of oxidising urea, providing a previously ignored source of nitrite. Here, we show that the relative magnitude of urea and ammonia oxidation rates, and the relative rates of N 2 O production from the two substrates, is correlated with the ratio of the substrate concentrations. By examining all reported measurements of urea and ammonium concentrations and the paired urea and ammonia oxidation rates, we show that this relationship likely holds across the global ocean. Examination of newly acquired and previously published metagenomic data shows that the fraction of AOA with the genetic capability for urea oxidation increases with the urea:ammonium ratio, rather than depending on the urea or ammonium concentration alone. These results corroborate the correlation between substrate ratios and oxidation rate ratios, and extend it to N 2 O production. This may help explain the distribution of nitrification rates and N 2 O production in the ocean.

Stratified enhanced interval-valued q-rung orthopair picture bipolar fuzzy decision-making approach for municipal solid waste disposal technique selection - T. N. Parthasarathy; C. S. Thilagasree; T. Jayakumar; V. Simic; D. Pamucar (International Journal of Environmental Science and Technology, 2025)

Length–Weight Relationship and Relative Condition Factor of 20 Carangid Fish Species from the Gulf of Mannar, Southeast Coast of India - J Joyson Paul; R Durairaja; N Jayakumar; K V. Venkataramani; Thangaraji Ravikumar; M Sharumathi; Kishore Kumar; Sanjay Chandravanshi; Adyasha Sahu; C Sudhan (Thalassas: An International Journal of Marine Sciences, 2025)

Spatio-temporal variations in the diversity and occurrence of lutjanid fish species (Family: Lutjanidae) of the Gulf of Mannar, Southeast coast of India - M. Sharumathi; N. Jayakumar; R. Durairaja; J. Joyson Paul; C. Sudhan; M. Kalaiarasan; L. Ranjith (Marine Biodiversity, 2025)

Length-Weight Relationships and Condition Factor of 15 Coastal Fish Species (Family: Lethrinidae) of the Gulf of Mannar, Southeast Coast of India - Sanjay Chandravanshi; N. Jayakumar; R. Durairaja; S. Aanand; E. Suresh; C. Sudhan; M. Kishore Kumar; Mahesh Chand Sonwal; Adyasha Sahu (Thalassas: An International Journal of Marine Sciences, 2025)

Physiological traits and population dynamics of Schizothorax niger (Heckel, 1838): Insights from Dal Lake and the Jhelum River, Kashmir, Himalayan region - Narayanan Karthik; Farooz Ahmad Bhat; Imtiyaz Qayoom; N. Jayakumar; C. Sudhan; P. Seenivasan; Divya Meril; Ishrat Mohd; Asra Mattoo (Journal of Fish Biology, 2025)
This study examines the physicochemical characteristics, morphometric features, biometric growth parameters, biological indices, physiological parameters, and biochemical profiles of Schizothorax niger population. The physicochemical analysis revealed a maximum temperature of 12.93 ± 1.33°C and hardness of 156.53 ± 12.82 mg/L in Dal Lake, whereas the Jhelum River had a minimum level of 10.94 ± 1.12°C temperature and 128.31 ± 11.62 mg/L of hardness. Dal Lake had a neutral pH (7.5 ± 0.2) and lower dissolved oxygen (6.8 ± 0.4 mg/L) compared to the Jhelum River (pH 7.2 ± 0.3; dissolved oxygen 7.5 ± 0.5 mg/L). Morphometric analysis showed significant differences ( p b = 3.15) than the Jhelum River ( b = 2.98). Biological indices revealed gender‐based variations in the gonado‐somatic index (GSI) and hepato‐somatic index (HSI), with GSI being higher in Dal Lake (0.21 ± 0.02) and HSI in the Jhelum River (1.04 ± 0.09). Haematological and biochemical analyses showed significant differences in parameters such as haematocrit (Dal Lake: 29.2 ± 2.1%; the Jhelum River: 32.4 ± 1.8%), glucose (Dal Lake: 85.3 ± 5.4 mg/dL; the Jhelum River: 68.1 ± 4.2 mg/dL), and total protein (Dal Lake: 6.2 ± 0.4 g/dL; the Jhelum River: 5.8 ± 0.3 g/dL) between sites. These findings provide valuable insights into the physiological traits and population dynamics of S. niger , informing species‐specific conservation strategies and ecosystem management practices.

Excess feeding increases adipogenesis but lowers leptin transcript abundance in zebrafish larvae - William Andrew Thompson; Jithine Jayakumar Rajeswari; Alison C. Holloway; Mathilakath M. Vijayan (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Comparative assessment of growth performance of indigenous and cross-bred calves subjected to combined stressors (heat and nutritional) - C. G. Shashank; R. G. Prashant; Parveen Kumar; Nitish A. Kulkarni; Manish Tiwari; S. Jayakumar; V. Sejian (International Journal of Biometeorology, 2023)

Etiology behind canine uterine inertia: Role of uterine expression of MLCK4, MYH2, and PKC genes - Magnus P.K.; Jayakumar C.; Naicy T.; Lali F.A.; Hiron M. Harshan; Abhilash R.S.; Ajithkumar S. (Animal Reproduction Science, 2023)

Toxicological effect of endocrine disrupting insecticide (deltamethrin) on enzymatical, haematological and histopathological changes in the freshwater iridescent shark, Pangasius hypothalamus - C. Prabhanjan Kumar Reddy; D. Manikandavelu; Ulaganathan Arisekar; B. Ahilan; A. Uma; N. Jayakumar; Woong Kim; Muthusamy Govarthanan; C. Harini; R. Sri Vidya; N. Madhavan; D. Ravindra Kumar Reddy (Environmental Toxicology and Pharmacology, 2023)

Nitrous oxide production in the Chesapeake Bay - Weiyi Tang; John C. Tracey; Julia Carroll; Elizabeth Wallace; Jenna A. Lee; Levy Nathan; Xin Sun; Amal Jayakumar; Bess B. Ward (Limnology and Oceanography, 2022)
Estuaries at the global scale are significant but highly uncertain sources of atmospheric nitrous oxide (N 2 O), which is an intense greenhouse gas and ozone depletion agent. As the largest estuary in the United States, the Chesapeake Bay is suggested to be a spatially and temporally variable source and sink of N 2 O. However, limited observations of N 2 O cycling preclude us from estimating and predicting its net N 2 O flux. To improve our mechanistic understanding of the processes that control the N 2 O flux at the point of production, we applied multiple 15 N tracers (, 15 N‐urea, and ) to separately track N 2 O production from nitrification and denitrification under in situ and manipulated O 2 concentrations in the Chesapeake Bay. Nitrification was the major N 2 O production pathway in oxic waters (up to 7.5 nmol N 2 O L −1 d −1 ). In contrast, denitrification dominated N 2 O production from hypoxic/anoxic waters (up to 20 nmol N 2 O L −1 d −1 ). N 2 O production from urea was observed for the first time in estuarine waters. The contribution from urea was small, but interestingly, showed a depth pattern distinct from other N 2 O precursors. Experimentally lowering the O 2 concentration substantially enhanced N 2 O production. Therefore, the expansion of hypoxic and anoxic zones in the Chesapeake Bay under climate change as suggested by some climate models may favor the production of N 2 O, potentially providing positive feedback on warming. Overall, our study provides mechanistic constraints on N 2 O dynamics that could benefit modeling studies to better estimate the N 2 O flux in the Chesapeake Bay and other coastal environments.

Pharmacological characterization of a structurally new class of antibacterial compound, triphenyl-phosphonium conjugated diarylheptanoid: Antibacterial activity and molecular mechanism - Shweta Kumari; Sundarraj Jayakumar; Subhash C Bihani; Neena Shetake; Raji Naidu; Vijay K Kutala; Haladhar D Sarma; Gagan D Gupta; Santosh K Sandur; Vinay Kumar (Journal of Biosciences, 2020)

Drought tolerant bacterial endophytes with potential plant probiotic effects from Ananas comosus - Aswathy Jayakumar; Pooja Padmakumar; Indu C. Nair; E. K. Radhakrishnan (Biologia, 2020)

Drought-tolerant and plant growth-promoting endophytic Staphylococcus sp. having synergistic effect with silicate supplementation - Aswathy Jayakumar; Arathy Krishna; Indu C. Nair; E. K. Radhakrishnan (Archives of Microbiology, 2020)

India’s contribution to mitigating the impacts of climate change through vegetation management - J. Dash; M. D. Behera; C. Jeganathan; C. S. Jha; S. Sharma; R. Lucas; A. A. Khuroo; A. Harris; P. M. Atkinson; D. S. Boyd; C. P. Singh; M. P. Kale; et al. (Tropical Ecology, 2020)

Interaction of glyoxal with collagenous matrix and its behavioral aspects for non-toxic and sustainable tanning system - J. Kanagaraj; R. C. Panda; G. C. Jayakumar (International Journal of Environmental Science and Technology, 2020)

Plant Growth Enhancement, Disease Resistance, and Elemental Modulatory Effects of Plant Probiotic Endophytic Bacillus sp. Fcl1 - Aswathy Jayakumar; Arathy Krishna; Mahesh Mohan; Indu C. Nair; E. K. Radhakrishnan (Probiotics and Antimicrobial Proteins, 2019)

Determining shallow aquifer vulnerability by the DRASTIC model and hydrochemistry in granitic terrain, southern India - N C Mondal; S Adike; V S Singh; S Ahmed; K V Jayakumar (Journal of Earth System Science, 2017)

Transdermal Delivery of Functional Collagen Via Polyvinylpyrrolidone Microneedles - Wenchao Sun; Mohammed Inayathullah; Martin A. C. Manoukian; Andrey V. Malkovskiy; Sathish Manickam; M. Peter Marinkovich; Alfred T. Lane; Lobat Tayebi; Alexander M. Seifalian; Jayakumar Rajadas (Annals of Biomedical Engineering, 2015)

Ion transport in broad bean leaf mesophyll under saline conditions - William J. Percey; Lana Shabala; Michael C. Breadmore; Rosanne M. Guijt; Jayakumar Bose; Sergey Shabala (Planta, 2014)

Mechanism of intraseasonal oceanic signature in the region off southern tip of India during boreal summer - A. Jayakumar; C. Gnanaseelan; T. P. Sabin (International Journal of Climatology, 2013)
Sea surface temperature (SST) in the region off southern tip of India (STI, 75–83°E, 5–8°N) exhibited a prominent variability in the intraseasonal time scale (both 30–90 d and 10–30 d band) during boreal summer. Mechanisms associated with this intraseasonal variability are studied using three‐dimensional ocean general circulation model (OGCM) sensitivity experiments, satellite observed outgoing longwave radiation, SST and winds for the period 1998–2007. The background oceanic structure of the STI characterized by a shallow thermocline and moderate mixed layer provided ideal conditions for strong oceanic sub‐surface processes. The model mixed layer heat budget reveals that the oceanic processes such as horizontal advection and vertical processes are the dominant mechanisms in the STI region as compared with air‐sea flux. Sensitivity experiments with the OGCM reveals that the ocean dynamical processes contribute to most of the intraseasonal SST variability and the wind stress contributes to 85% of the variability whereas surface flux contributes to only 15% for the 30–90 d SST variability. Higher amplitude of surface flux perturbation and its contribution to SST in the 10–30 d as compared with the 30–90 d band are evident in the model experiment and are consistent with the observational analysis. There is year‐to‐year variability in the relative role of horizontal and vertical processes for different intraseasonal SST events over STI.

Distinctive effects of nano-sized permethrin in the environment - R. S. Suresh Kumar; P. J. Shiny; C. H. Anjali; Jayakumar Jerobin; Katrin Margulis Goshen; Shlomo Magdassi; Amitava Mukherjee; N. Chandrasekaran (Environmental Science and Pollution Research, 2013)

Processes of 30–90 days sea surface temperature variability in the northern Indian Ocean during boreal summer - J. Vialard; A. Jayakumar; C. Gnanaseelan; M. Lengaigne; D. Sengupta; B. N. Goswami (Climate Dynamics, 2012)

Processes controlling the surface temperature signature of the Madden–Julian Oscillation in the thermocline ridge of the Indian Ocean - A. Jayakumar; Jérôme Vialard; M. Lengaigne; C. Gnanaseelan; Julian P. McCreary; B. Praveen Kumar (Climate Dynamics, 2011)

Intraseasonal signals in the daily high resolution blended Reynolds sea surface temperature product over the tropical Indian Ocean and their validation - B. H. Vaid; C. Gnanaseelan; A. Jayakumar (International Journal of Remote Sensing, 2011)

Influence of the macrotidal environment on the source to sink pathways of suspended flux in the Gulf of Kachchh, India: evidence from the Ocean Colour Monitor (IRS‐P4) - O. S. Chauhan; A. A. A. Menezes; S. Jayakumar; M. A. Malik; Y. Pradhan; A. S. Rajawat; S. R. Nayak; G. Bandekar; C. Almeida; M. Talaulikar; M. V. Ramanamurty; B. R. Subramanian (International Journal of Remote Sensing, 2007)

Detection of Rabies Virus Genes by In-Situ Polymerase Chain Reaction - P. Ezhil Praveena; R. Jayakumar; C. Balachandran; G. Thirumurugan; G. Dhinakar Raj; B. Murali Manohar (Veterinary Research Communications, 2007)

Differential response ofAzolla microphylla kaulf. andAzolla filiculoides Lam. to sodium fluoride - M. Eyini; K. Sujanandini; C. Pothiraj; M. Jayakumar; Bong -Seop Kil (Journal of Plant Biology, 1999)